2020
DOI: 10.1186/s41983-020-00211-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin in patients with relapsing remitting multiple sclerosis

Abstract: Background: Multiple sclerosis (MS) is an inflammatory demyelinating disorder that affects the central nervous system (CNS) of females more than males. The objective of the current study was to assess serum level of prolactin (PRL) and tumor necrosis factor alpha (TNFα) in patients with relapsing remitting multiple sclerosis (RRMS) and to explore their role in disease activity. Subjects and methods: Fifty females were included in this study, 40 patients with RRMS were evaluated during relapse and remission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As prolactin plays a dual role in MS immune pathogenesis, it influences CD40 expression in B cells and increases B cell autoreactivity in MS, which may demonstrate a link between brain injury and prolactin levels by enhancing myelin regeneration and neuronal survival in MS animal models. [ 43 ]. As such, a possible explanation for our results might be that tele-Pilates and tele-yoga may help female patients with MS to repair their myelin by increasing prolactin serum levels [ 43 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As prolactin plays a dual role in MS immune pathogenesis, it influences CD40 expression in B cells and increases B cell autoreactivity in MS, which may demonstrate a link between brain injury and prolactin levels by enhancing myelin regeneration and neuronal survival in MS animal models. [ 43 ]. As such, a possible explanation for our results might be that tele-Pilates and tele-yoga may help female patients with MS to repair their myelin by increasing prolactin serum levels [ 43 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, a possible explanation for our results might be that tele-Pilates and tele-yoga may help female patients with MS to repair their myelin by increasing prolactin serum levels [ 43 , 63 ]. In contrast, it has been indicated that an increase in prolactin levels may also raise inflammatory reactions and injure MS patients [ 43 , 64 ]. Eventually, to develop a full picture of prolactin’s role in MS patients after exercise, additional studies will be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed a significant increase in TNF‐α levels in MS patients in relapse compared to control but no difference in its level between patients in remission and control subjects. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%